Electrolyte composition, quasi-solid electrolyte, and lithium-ion battery using the same
By preparing polymer pseudo-solid electrolytes containing specific repeating units, the low energy density and safety problems of liquid lithium-ion batteries are solved, and the inhibition of lithium dendrites and the improvement of ionic conductivity is achieved.
Patent Information
- Application Number
- JP2023070694
- Authority / Receiving Office
- JP · JP
- Patent Type
- Patents
- Current Assignee / Owner
- Priority Date
- 2022-11-15
- Filing Date
- 2023-04-24
- Publication Date
- 2025-02-04
- Estimated Expiration
- 2043-04-24
AI Technical Summary
Existing liquid lithium-ion batteries have low energy density and limited cycle life. Increased energy density will increase safety risks, such as the risk of battery expansion, heat generation, combustion or explosion. At the same time, the high surface resistance of traditional electrolytes hinders battery performance improvement.
The polymer containing specific repeat units prepared by ring polymerization is formed into a pseudo-solid electrolyte. By combining components (a), (b), and (c), the first and second polymers or the third polymers are formed, a three-dimensional network structure is formed, lithium salts and solvents are adsorbed, the surface resistance of the electrolyte is reduced and the growth of lithium dendrites is inhibited.
The safety of the battery is improved, the growth of lithium dendrites is suppressed, the safety of the battery is enhanced, and the ionic conductivity is improved by reducing the surface resistance of the electrolyte.
Smart Images

Figure 0007626792000033 
Figure 0007626792000001 
Figure 0007626792000002
Abstract
Description
[Technical field]
[0001] The present disclosure relates to an electrolyte composition, a quasi-solid electrolyte, and a lithium-ion battery using the same. [Background technology]
[0002] Lithium-ion batteries have become the mainstream of commercial batteries, and efforts are being made to make them lighter, thinner, smaller, have higher energy density, have longer life, and are safer. [Prior art documents] [Patent documents]
[0003] [Patent Document 1] US Patent Application Publication No. 2005 / 0042515A1 Summary of the Invention [Problem to be solved by the invention]
[0004] The current liquid lithium-ion batteries have a low gravimetric energy density and limited cycle life, which keeps the unit energy storage cost high. However, if the energy density of the battery is increased without considering other factors, the speed at which a series of safety problems of electrochemical batteries, such as leakage, battery expansion, heat generation, smoke generation, combustion, or explosion, is easily induced will increase, greatly limiting the usability.
[0005] On the other hand, when the operating voltage of a lithium-ion battery is increased, the oxidation reaction of the electrolyte is easily accelerated, which leads to poor stability during high-voltage charging of the battery. The industry has further proposed using polymers as electrolyte additives to improve stability, but the polymers used in conventional electrolytes still have a high interfacial impedance in the electrolyte system and cannot effectively achieve the combustion suppression effect.
[0006] Therefore, there is a need in the industry for new electrolytes to be used in lithium ion batteries to solve the above problems. [Means for solving the problem]
[0007] The present disclosure provides an electrolyte composition that can be subjected to a ring-opening polymerization reaction to obtain a quasi-solid electrolyte for use in a battery. The electrolyte composition may include components (A), (B), and (C), and the content of component (A) is 1 wt% to 10 wt% based on the total weight of components (A), (B), and (C). Component (A) may be a combination of a first polymer (A1) and a second polymer (A2), or component (A) may be a third polymer (A3). The first polymer (A1) may have a repeating unit represented by formula (I), the second polymer (A2) may have a repeating unit represented by formula (II), and the third polymer (A3) may have a repeating unit represented by formula (I) and a repeating unit represented by formula (II).
[0008] [ka]
[0009] In the formula, R 1 may be hydrogen or a methyl group, R 2 may be an oxiranyl group, a methyloxiranyl group, a glycidyl group, a methylglycidyl group, an oxetanyl group, or a (3,4-epoxycyclohexyl)methyl group; Z 1 is C 1-10 Alkanediyl groups, [ka] where n>1 and Z 2 is C 1-10alkanediyl group, R 3 may be hydrogen or a methyl group, R 4 and R 5 are each independently C 1-10 Alkyl group, C 1-10 Alkoxy group, C 4-8 Cycloalkyl group, C 4-8 Cycloalkoxy group, C 5-12 Cycloalkylalkyl group, C 5-12 R may be a cycloalkylalkoxy group, a substituted or unsubstituted phenyl group, a substituted or unsubstituted phenoxy group, a substituted or unsubstituted benzyl group, or a substituted or unsubstituted benzyloxy group. 4 may be a substituted or unsubstituted phenyl group, R 5 may be a substituted or unsubstituted phenoxy group, and R 4 and R 5 forms a six-membered ring with the phosphorus atom to which it is bonded, and Z 3 is C 1-10 Alkanediyl groups, [ka] and Z 4 , Z 5 , and Z 6 are each independently C 1-10 Component (B) may be an alkanediyl group, m>1, and i>1. Component (B) may be a lithium salt, and component (C) may be a solvent. According to an embodiment of the present disclosure, the weight ratio of the lithium salt to the solvent is 1:19 to 7:13.
[0010] According to an embodiment of the present disclosure, the present disclosure provides a quasi-solid-state electrolyte, which can be a product of a ring opening polymerization reaction of the above-mentioned electrolyte composition of the present disclosure.
[0011] According to another embodiment of the present disclosure, the present disclosure provides a lithium ion battery, for example a lithium ion secondary battery. The lithium ion battery may include a positive electrode, a negative electrode, a separator, and the above-mentioned quasi-solid electrolyte. The separator may be disposed between the positive electrode and the negative electrode, and the quasi-solid electrolyte may be disposed between the positive electrode and the negative electrode. Effect of the Invention
[0012] The present disclosure provides an electrolyte composition. Since the electrolyte composition according to the present disclosure is liquid, it can be easily injected into the battery chamber. In addition, the electrolyte composition according to the present disclosure can be converted from a liquid electrolyte composition to a quasi-solid electrolyte by a ring-opening polymerization reaction. The quasi-solid electrolyte according to the present disclosure has a phosphorus-containing polymer, which can prevent the volatilization of the electrolyte and the growth of lithium dendrites, and also achieves the technical effect of suppressing combustion, thereby enhancing the safety of the battery. In addition, the quasi-solid electrolyte according to the present disclosure includes a polymer (which easily adsorbs lithium salt and solvent) having a three-dimensional mesh structure, and the amount of polymer used can be reduced, so that the interface impedance of the electrolyte can be reduced and the ionic conductivity of the electrolyte can be increased. According to an embodiment of the present disclosure, the present disclosure also provides a lithium ion battery including the quasi-solid electrolyte. The specific components of the quasi-solid electrolyte according to the present disclosure provide the quasi-solid electrolyte according to the present disclosure with a combustion suppressing property, thereby improving the safety of the battery in use.
[0013] A detailed description will be given in the following embodiments.
[0014] The present disclosure is best understood from the following detailed description when read in conjunction with the accompanying drawings, in which: It should be emphasized that, according to common practice in the industry, various features have not been drawn to scale, and in fact, dimensions of various features may be arbitrarily increased or decreased for clarity of presentation. [Brief description of the drawings]
[0015] [Figure 1] FIG. 1 is a schematic diagram of a lithium ion battery of the present disclosure. DETAILED DESCRIPTION OF THE PREFERRED EMBODIMENTS
[0016] The electrolyte composition, quasi-solid electrolyte, and lithium ion battery containing the same of the present disclosure will be described in detail below. It should be understood that many different embodiments or examples are presented below so that different aspects of the present disclosure can be implemented. The specific components and configurations described below are merely for the purpose of simplifying the present disclosure. Of course, these are merely examples and do not limit the present disclosure. In the present disclosure, the term "about" refers to an amount that is increased or decreased by a magnitude that would be considered normal and reasonable by a person skilled in the art from a given amount.
[0017] Furthermore, in the drawings, the shape or thickness of the embodiment may be exaggerated and may be simplified or displayed for convenience. Also, the parts of each component in the drawings are described separately. It should be noted that components not shown or depicted in the drawings are of a type known to those having ordinary skill in the art. Also, the specific embodiment is merely used to disclose a specific method used in the present disclosure, and is not used to limit the present disclosure.
[0018] Furthermore, ordinal numbers used in the specification and claims, such as "first," "second," "third," etc., modify elements of a claim and do not, by themselves, imply or represent that the element in that claim has an ordinal number preceding it, nor do they represent an order of elements in one claim relative to elements in another claim, or an order of a method of manufacture. These ordinal numbers are used only so that elements in a claim having a certain name may be clearly distinguished from elements in other claims having the same name.
[0019] According to an embodiment of the present disclosure, the present disclosure provides an electrolyte composition, which can be subjected to a ring-opening polymerization reaction (e.g., a heating process) to obtain a quasi-solid electrolyte for use in a battery.
[0020] The electrolyte composition may include component (A), component (B), and component (C). Component (A) may be a combination of a first polymer (A1) and a second polymer (A2), or component (A) may be a third polymer (A3). The first polymer (A1) may have a repeat unit represented by formula (I), the second polymer (A2) may have a repeat unit represented by formula (II), and the third polymer (A3) may have a repeat unit represented by formula (I) and a repeat unit represented by formula (II).
[0021] [ka]
[0022] In the formula, R 1 may be hydrogen or a methyl group, R 2may be an oxiranyl group, a methyloxiranyl group, a glycidyl group, a methylglycidyl group, an oxetanyl group, or a (3,4-epoxycyclohexyl)methyl group; Z 1 is C 1-10 Alkanediyl groups, [ka] where n>1 (e.g., 5000≧n>1, 3000≧n>1, 2000≧n>1, 1000≧n>1, or 500≧n>1), and Z 2 is C 1-10 alkanediyl group, R 3 may be hydrogen or a methyl group, R 4 and R 5 are each independently C 1-10 Alkyl group, C 1-10 Alkoxy group, C 4-8 Cycloalkyl group, C 4-8 Cycloalkoxy group, C 5-12 Cycloalkylalkyl group, C 5-12 R may be a cycloalkylalkoxy group, a substituted or unsubstituted phenyl group, a substituted or unsubstituted phenoxy group, a substituted or unsubstituted benzyl group, or a substituted or unsubstituted benzyloxy group. 4 may be a substituted or unsubstituted phenyl group, R 5 may be a substituted or unsubstituted phenoxy group, and R 4and R 5 forms a six-membered ring with the phosphorus atom to which Z is bonded, 3 is C 1-10 Alkanediyl groups, [ka] and Z 4 , Z 5 , and Z 6 are each independently C 1-10 It may be an alkanediyl group, where m>1 (e.g., 5000≧m>1, 3000≧m>1, 2000≧m>1, 1000≧m>1, or 500≧m>1) and i>1 (e.g., 5000≧i>1, 3000≧i>1, 2000≧i>1, 1000≧i>1, or 500≧i>1). Component (B) may be a lithium salt, and component (C) may be a solvent.
[0023] According to an embodiment of the present disclosure, the first polymer (A1), the second polymer (A2), and the third polymer (A3) are all different. According to an embodiment of the present disclosure, the first polymer (A1) can be a homopolymer, i.e., the first polymer (A1) does not contain any other repeating units besides the repeating units represented by formula (I). According to an embodiment of the present disclosure, the second polymer (A2) can also be a homopolymer, i.e., the second polymer (A2) does not contain any other repeating units besides the repeating units represented by formula (II). According to an embodiment of the present disclosure, the third polymer (A3) is a heteropolymer, and the third polymer (A3) does not contain any other repeating units besides the repeating units represented by formula (I) and the repeating units represented by formula (II). Also, according to some embodiments of the present disclosure, in the third polymer (A3), the repeating unit represented by formula (I) and the repeating unit represented by formula (II) are arranged in a block manner. According to other embodiments of the present disclosure, in the third polymer (A3), the repeating unit represented by formula (I) and the repeating unit represented by formula (II) are arranged in a random manner.
[0024] According to an embodiment of the present disclosure, C 1-10 The alkanediyl group can be a linear or branched alkanediyl group. Examples include C 1-10 The alkanediyl group can be a methanediyl group, an ethanediyl group, a propanediyl group, a butanediyl group, a pentanediyl group, a hexanediyl group, a heptanediyl group, an octanediyl group, a nonanediyl group, a decanediyl group, or an isomer thereof.
[0025] According to an embodiment of the present disclosure, C 1-10 The alkyl group may be a linear or branched alkyl group. Examples include C 1-10 The alkyl group can be a methyl group, an ethyl group, a propyl group, a butyl group, a pentyl group, a hexyl group, a heptyl group, an octyl group, a nonyl group, a decyl group, or an isomer thereof.
[0026] According to an embodiment of the present disclosure, C 1-10 The alkoxy group may be a linear or branched chain alkoxy group. Examples include C 1-10The alkoxy group can be a methoxy group, an ethoxy group, a propoxy group, a butoxy group, a pentoxy group, a hexoxy group, a heptoxy group, an octoxy group, a nonoxy group, a decoxy group, or an isomer thereof.
[0027] According to an embodiment of the present disclosure, C 4-8 The cycloalkyl group can be a cyclobutyl group, a cyclopentyl group, a cyclohexyl group, a cycloheptyl group, or a cyclooctyl group.
[0028] According to an embodiment of the present disclosure, C 4-8 The cycloalkoxy group may be a cyclobutoxy group, a cyclopentoxy group, a cyclohexoxy group, a cycloheptoxy group, or a cyclooctoxy group.
[0029] According to an embodiment of the present disclosure, C 5-12 Cycloalkylalkyl groups are substituted C 1-4 It may be an alkyl group (e.g., methyl, ethyl, propyl, or butyl). 1-4 An alkyl group is one in which the hydrogen on at least one carbon of the alkyl group is C 4-8It refers to one substituted with a cycloalkyl group.
[0030] According to an embodiment of the present disclosure, C 5-12 A cycloalkylalkoxy group is a substituted C 1-4 It may be an alkoxy group (e.g., methoxy, ethoxy, propoxy, or butoxy). 1-4 An alkoxy group is one in which the hydrogen on at least one carbon of the alkoxy group is C 4-8 It refers to one substituted with a cycloalkyl group.
[0031] According to an embodiment of the present disclosure, a substituted phenyl group according to the present disclosure is a phenyl group in which the hydrogen on at least one carbon of the phenyl group is replaced with a C 1-4 According to an embodiment of the present disclosure, a substituted phenoxy group according to the present disclosure refers to a group in which the hydrogen on at least one carbon of the phenoxy group is replaced with a C 1-4 According to an embodiment of the present disclosure, a substituted benzyl group according to the present disclosure refers to a benzyl group in which the hydrogen on at least one carbon of the benzyl group is replaced with a C 1-4 According to an embodiment of the present disclosure, a substituted benzyloxy group according to the present disclosure refers to a benzyloxy group in which the hydrogen on at least one carbon of the benzyloxy group is replaced with a C 1-4 This refers to a group substituted with an alkyl group.
[0032] According to an embodiment of the present disclosure, the repeat unit represented by formula (I) according to the present disclosure can be any of the following:
[0033] [ka]
[0034] In the formula, Z 1 is a methanediyl group, an ethanediyl group, a propanediyl group (e.g., a linear or branched propanediyl group), a butanediyl group (e.g., a linear or branched butanediyl group), a pentanediyl group (e.g., a linear or branched pentanediyl group), a hexanediyl group (e.g., a linear or branched hexanediyl group), a heptanediyl group (e.g., a linear or branched heptanediyl group), an octanediyl group (e.g., a linear or branched octanediyl group), a nonanediyl group (e.g., a linear or branched nonanediyl group), or a decanediyl group. group) (e.g., a linear or branched decanediyl group), and R 2 may be an oxiranyl group, a methyloxiranyl group, a glycidyl group, a methylglycidyl group, an oxetanyl group, or a (3,4-epoxycyclohexyl)methyl group.
[0035] According to an embodiment of the present disclosure, the repeat unit of formula (I) according to the present disclosure may be any of the following:
[0036] [ka]
[0037] In the formula, R 2may be an oxiranyl group, a methyloxiranyl group, a glycidyl group, a methylglycidyl group, an oxetanyl group, or a (3,4-epoxycyclohexyl)methyl group, n>1, and Z 2 is a methanediyl group, an ethanediyl group, a propanediyl group (e.g., a linear or branched propanediyl group), a butanediyl group (e.g., a linear or branched butanediyl group), a pentanediyl group (e.g., a linear or branched pentanediyl group), a hexanediyl group (e.g., a linear or branched hexanediyl group), a heptanediyl group (e.g., a linear or branched heptanediyl group), an octanediyl group (e.g., a linear or branched octanediyl group), a nonanediyl group (e.g., a linear or branched nonanediyl group), or a decanediyl group. It may be a aryl group (e.g., a straight or branched chain decanediyl group).
[0038] According to some embodiments of the present disclosure, the repeat unit of formula (I) according to the present disclosure may be any of the following:
[0039] [ka]
[0040] In the formula, Z 1 is C 1-10 Alkanediyl groups, [ka] where n>1 (e.g., 5000≧n>1, 3000≧n>1, 2000≧n>1, 1000≧n>1, or 500≧n>1), and Z 2 is C 1-10 It may be an alkanediyl group.
[0041] According to an embodiment of the present disclosure, the repeat unit of formula (II) according to the present disclosure may be:
[0042] [ka]
[0043] In the formula, Z 3 is a methanediyl group, an ethanediyl group, a propanediyl group (e.g., a linear or branched propanediyl group), a butanediyl group (e.g., a linear or branched butanediyl group), a pentanediyl group (e.g., a linear or branched pentanediyl group), a hexanediyl group (e.g., a linear or branched hexanediyl group), a heptanediyl group (e.g., a linear or branched heptanediyl group), an octanediyl group (e.g., a linear or branched octanediyl group), a nonanediyl group (e.g., a linear or branched nonanediyl group), or a decanediyl group. group) (e.g., a linear or branched decanediyl group), and R 4 and R 5 are each independently C 1-10 Alkyl group, C 1-10 Alkoxy group, C 4-8 Cycloalkyl group, C 4-8 Cycloalkoxy group, C5-12 Cycloalkylalkyl group, C 5-12 In some embodiments of the present disclosure, R may be a cycloalkylalkoxy group, a substituted or unsubstituted phenyl group, a substituted or unsubstituted phenoxy group, a substituted or unsubstituted benzyl group, or a substituted or unsubstituted benzyloxy group. 4 is a substituted or unsubstituted phenyl group, and R 5 is a substituted or unsubstituted phenoxy group, R 4 and R 5 can form a six-membered ring with the phosphorus atom to which it is bonded.
[0044] According to an embodiment of the present disclosure, R 4 and R 5are each independently a methyl group, an ethyl group, a propyl group (e.g., a straight-chain or branched-chain propyl group), a butyl group (e.g., a straight-chain or branched-chain butyl group), a pentyl group (e.g., a straight-chain or branched-chain pentyl group), a hexyl group (e.g., a straight-chain or branched-chain hexyl group), a heptyl group (e.g., a straight-chain or branched-chain heptyl group), an octyl group (e.g., a straight-chain or branched-chain octyl group), a nonyl group (e.g., a straight-chain or branched-chain nonyl group), a decyl group (e.g., a straight-chain or branched-chain decyl group), a methoxy group, an ethoxy group, a propoxy group (e.g., a straight-chain or branched-chain propoxy group), a butoxy group, group (e.g., straight or branched chain butoxy), pentoxy group (e.g., straight or branched chain pentoxy), hexoxy group (e.g., straight or branched chain hexoxy), heptoxy group (e.g., straight or branched chain heptoxy), octoxy group (e.g., straight or branched chain octoxy), nonoxy group (e.g., straight or branched chain nonoxy), decoxy group (e.g., straight or branched chain decoxy), cyclobutyl group, cyclopentyl group, cyclohexyl group, cycloheptyl group, cyclooctyl group, cyclobutoxy group, cyclopentoxy group), cyclohexoxy group, cycloheptoxy groupThe aryl group may be a cyclooctoxy group, a cyclooctoxy group, a phenyl group, a phenoxy group, a benzyl group, or a benzyloxy group.
[0045] According to an embodiment of the present disclosure, the repeat unit represented by formula (II) according to the present disclosure may be any of the following:
[0046] [ka]
[0047] In the formula, Z 4 , Z 5 , and Z 6 are each independently a methanediyl group, an ethanediyl group, a propanediyl group (e.g., a linear or branched propanediyl group), a butanediyl group (e.g., a linear or branched butanediyl group), a pentanediyl group (e.g., a linear or branched pentanediyl group), a hexanediyl group (e.g., a linear or branched hexanediyl group), a heptanediyl group (e.g., a linear or branched heptanediyl group), an octanediyl group (e.g., a linear or branched octanediyl group), a nonanediyl group (e.g., a linear or branched nonanediyl group), or a decanediyl group. m>1 (e.g., 5000≧m>1, 3000≧m>1, 2000≧m>1, 1000≧m>1, or 500≧m>1), and i>1 (e.g., 5000≧i>1, 3000≧i>1, 2000≧i>1, 1000≧i>1, or 500≧i>1), R4 and R 5 are each independently C 1-10 Alkyl group, C 1-10 Alkoxy group, C 4-8 Cycloalkyl group, C 4-8 Cycloalkoxy group, C 5-12 Cycloalkylalkyl group, C 5-12 In some embodiments of the present disclosure, R may be a cycloalkylalkoxy group, a substituted or unsubstituted phenyl group, a substituted or unsubstituted phenoxy group, a substituted or unsubstituted benzyl group, or a substituted or unsubstituted benzyloxy group. 4 is a substituted or unsubstituted phenyl group, R 5 is a substituted or unsubstituted phenoxy group, R 4 and R 5 can form a six-membered ring with the phosphorus atom to which it is bonded.
[0048] According to an embodiment of the present disclosure, the repeat unit represented by formula (II) according to the present disclosure may be any of the following:
[0049] [ka]
[0050] In the formula, R 3 is hydrogen or a methyl group, and Z 3 is C 1-10 Alkanediyl groups, [ka] and Z 4 , Z 5 , and Z6 are each independently a methanediyl group, an ethanediyl group, a propanediyl group (e.g., a linear or branched propanediyl group), a butanediyl group (e.g., a linear or branched butanediyl group), a pentanediyl group (e.g., a linear or branched pentanediyl group), a hexanediyl group (e.g., a linear or branched hexanediyl group), a heptanediyl group (e.g., a linear or branched heptanediyl group), an octanediyl group (e.g., a linear or branched octanediyl group), a nonanediyl group (e.g., a linear or branched nonanediyl group), or a decanediyl group. m>1 (e.g., 5000≧m>1, 3000≧m>1, 2000≧m>1, 1000≧m>1, or 500≧m>1), i>1 (e.g., 5000≧i>1, 3000≧i>1, 2000≧i>1, 1000≧i>1, or 500≧i>1), R 6 , R 7 , and R 8 are each independently a methyl group, an ethyl group, a propyl group (e.g., a straight-chain or branched-chain propyl group), a butyl group (e.g., a straight-chain or branched-chain butyl group), a pentyl group (e.g., a straight-chain or branched-chain pentyl group), a hexyl group (e.g., a straight-chain or branched-chain hexyl group), a heptyl group (e.g., a straight-chain or branched-chain heptyl group), an octyl group (e.g., a straight-chain or branched-chain octyl group), a nonyl group (e.g., a straight-chain or branched-chain nonyl group), or a decyl group (e.g., a straight-chain or branched-chain decyl group).
[0051] According to an embodiment of the present disclosure, the component (A) may be composed of a first polymer (A1) and a second polymer (A2), and the first polymer (A1) and the second polymer (A2) are different. According to an embodiment of the present disclosure, the weight ratio of the first polymer (A1) and the second polymer (A2) can be 1:4 to 4:1, for example, 1:3, 1:2, 1:1, 2:1, or 3:1. If the content of the first polymer (A1) is too low, the solvent adsorption of the quasi-solid electrolyte formed from the obtained electrolyte composition is reduced, and the electrolyte cannot be solidified. If the content of the first polymer (A1) is too high, the quasi-solid electrolyte formed from the obtained electrolyte composition is likely to form a dense network structure, and the interface impedance is increased, resulting in a decrease in ion conductivity. If the content of the second polymer (A2) is too low, the combustion suppression of the quasi-solid electrolyte formed from the obtained electrolyte composition is reduced.
[0052] According to an embodiment of the present disclosure, component (A) is a third polymer (A3). In the third polymer (A3), the ratio of the number of repeating units represented by formula (I) and the number of repeating units represented by formula (II) is 1:4 to 4:1, for example, 1:3, 1:2, 1:1, 2:1, or 3:1. If the number of repeating units represented by formula (I) is too small, the solvent adsorption of the quasi-solid electrolyte formed from the obtained electrolyte composition is reduced, and the electrolyte cannot be solidified (or gelled). If the number of repeating units represented by formula (I) is too large, the quasi-solid electrolyte formed from the obtained electrolyte composition is likely to form a dense network structure, and the interface impedance is increased, resulting in a decrease in ion conductivity. If the number of repeating units represented by formula (II) is too small, the combustion suppression of the quasi-solid electrolyte formed from the obtained electrolyte composition is reduced.
[0053] According to an embodiment of the present disclosure, the first polymer (A1) may be a product of a reaction (e.g., polymerization) of a first composition. The first composition may include a first monomer and an initiator, and the first monomer may have a structure shown in formula (III).
[0054] [ka]
[0055] In the formula, R 1 is hydrogen or a methyl group, and R 2 is an oxiranyl group, a methyloxiranyl group, a glycidyl group, a methylglycidyl group, an oxetanyl group, or a (3,4-epoxycyclohexyl)methyl group, and Z 1 is C 1-10 Alkanediyl groups, [ka] and n>1 (e.g., 5000≧n>1, 3000≧n>1, 2000≧n>1, 1000≧n>1, or 500≧n>1), and Z 2 is C 1-10 It is an alkanediyl group. According to an embodiment of the present disclosure, the first polymer (A1) is a homopolymer prepared from a first monomer.
[0056] According to an embodiment of the present disclosure, the first monomer may be glycidyl acrylate, glycidyl methacrylate (GMA), 2-hydroxyethyl acrylate glycidyl ether, 2-hydroxyethyl methacrylate glycidyl ether, 4-hydroxybutyl acrylate glycidyl ether, 4-hydroxybutyl methacrylate glycidyl ether, methylglycidyl acrylate, methylglycidyl methylacrylate, 3,4-epoxycyclohexylmethyl acrylate, or 3,4-epoxycyclohexylmethyl methacrylate.
[0057] According to an embodiment of the present disclosure, the weight average molecular weight (Mw) of the first polymer (A1) according to the present disclosure can be about 500 (g / mol) to 200000 (g / mol), for example, about 1000 (g / mol), 2000 (g / mol), 5000 (g / mol), 10000 (g / mol), 20000 (g / mol), 50000 (g / mol), or 150000 (g / mol). The weight average molecular weight (Mw) of the first polymer (A1) according to the present disclosure can be measured by gel permeation chromatography (GPC) (a calibration curve is created using polystyrene as a standard).
[0058] According to an embodiment of the present disclosure, the first composition may consist of a first monomer and an initiator. According to an embodiment of the present disclosure, the initiator can initiate a polymerization reaction on the acrylate (or methacrylate) groups of the first monomer. For example, the initiator may be a photoinitiator, a thermal initiator, or a combination thereof. According to an embodiment of the present disclosure, the content of the initiator can be about 0.01 wt% to 20 wt% (e.g., 0.1 wt%, 0.5 wt%, 1 wt%, 2 wt%, 3 wt%, 4 wt%, 5 wt%, 6 wt%, 7 wt%, 8 wt%, 9 wt%, 10 wt%, 11 wt%, 12 wt%, 13 wt%, 14 wt%, 15 wt%, 16 wt%, 17 wt%, 18 wt%, or 19 wt%) based on the total weight of the first monomer.
[0059] According to an embodiment of the present disclosure, the first composition is reacted at 20° C. to 150° C. for 60 minutes to 24 hours to cause the first composition to undergo a homopolymerization reaction, thereby obtaining the first polymer (A1).
[0060] According to an embodiment of the present disclosure, the second polymer (A2) may be a product of a reaction (e.g., polymerization) of a second composition. The second composition may include a second monomer and an initiator, and the second monomer may have a structure shown in formula (IV).
[0061] [ka]
[0062] R in the formula 3 may be hydrogen or a methyl group, R 4 and R 5 are each independently C 1-10 Alkyl group, C 1-10 Alkoxy group, C 4-8 Cycloalkyl group, C 4-8 Cycloalkoxy group, C 5-12Cycloalkylalkyl group, C 5-12 R may be a cycloalkylalkoxy group, a substituted or unsubstituted phenyl group, a substituted or unsubstituted phenoxy group, a substituted or unsubstituted benzyl group, or a substituted or unsubstituted benzyloxy group. 4 may be a substituted or unsubstituted phenyl group, R 5 may be a substituted or unsubstituted phenoxy group, and R 4 and R 5 forms a six-membered ring with the phosphorus atom to which Z is bonded, 3 is C 1-10 Alkanediyl groups, [ka] and Z 4 , Z 5 , and Z 6 are each independently C 1-10 It may be an alkanediyl group, where m≧1 (e.g., 5000≧m≧1, 3000≧m≧1, 2000≧m≧1, 1000≧m≧1, or 500≧m≧1) and i≧1 (e.g., 5000≧i≧1, 3000≧i≧1, 2000≧i≧1, 1000≧i≧1, or 500≧i≧1). According to an embodiment of the present disclosure, the second polymer (A2) is a homopolymer obtained by preparing a second monomer.
[0063] According to an embodiment of the present disclosure, the weight average molecular weight (Mw) of the second polymer (A2) according to the present disclosure can be about 500 (g / mol) to 200000 (g / mol), for example, about 1000 (g / mol), 2000 (g / mol), 5000 (g / mol), 10000 (g / mol), 20000 (g / mol), 50000 (g / mol), or 150000 (g / mol). The weight average molecular weight (Mw) of the second polymer (A2) according to the present disclosure can be measured by gel permeation chromatography (GPC) (a calibration curve is created using polystyrene as a standard).
[0064] According to an embodiment of the present disclosure, the second composition may comprise a second monomer and an initiator. According to an embodiment of the present disclosure, the initiator can initiate a polymerization reaction on the acrylate group (methacrylate group or alkenyl group) of the second monomer. For example, the initiator may be a photoinitiator, a thermal initiator, or a combination thereof. According to an embodiment of the present disclosure, the content of the initiator can be about 0.01 wt% to 10 wt% (e.g., 0.1 wt%, 0.5 wt%, 1 wt%, 2 wt%, 3 wt%, 4 wt%, 5 wt%, 6 wt%, 7 wt%, 8 wt%, or 9 wt%) based on the total weight of the second monomer.
[0065] According to an embodiment of the present disclosure, the second composition can be reacted at 20° C. to 150° C. for 60 minutes to 24 hours to cause the second composition to undergo a homopolymerization reaction to obtain a second polymer (A2).
[0066] According to an embodiment of the present disclosure, the second monomer is selected from the group consisting of diethyl allyl phosphate, diethyl allyl phosphonate, diethyl 2-(acryloyloxy)ethyl phosphate, diethyl 2-(methacryloyloxy)ethyl phosphate, dibutyl 2-(acryloyloxy)ethyl phosphate, dibutyl 2-(methacryloyloxy)ethyl phosphate, diphenyl 2-(acryloyloxy)ethyl phosphate, diphenyl 2-(acryloyloxy)ethyl phosphate, diphenyl 2-(methacryloyloxy)ethyl phosphate, 2-(methacryloyloxy)ethyl phosphate, (6-Oxido-6H-dibenz[c,e][1,2]oxaphosphorin-6-yl)methyl acrylate, or (6-Oxido-6H-dibenz[c,e][1,2]oxaphosphorin-6-yl)methyl methacrylate.
[0067] According to an embodiment of the present disclosure, the third polymer (A3) can be a product of a reaction (e.g., copolymerization) of a third composition. The third composition can include a first monomer, a second monomer, and an initiator. According to an embodiment of the present disclosure, the third polymer (A3) is a copolymer made from a first monomer and a second monomer.
[0068] According to an embodiment of the present disclosure, the weight average molecular weight (Mw) of the third polymer (A3) according to the present disclosure can be about 500 (g / mol) to 500000 (g / mol), for example, about 1000 (g / mol), 2000 (g / mol), 5000 (g / mol), 10000 (g / mol), 20000 (g / mol), 50000 (g / mol), 150000 (g / mol), 200000 (g / mol), 300000 (g / mol), or 400000 (g / mol). The weight average molecular weight (Mw) of the third polymer (A3) according to the present disclosure can be measured by gel permeation chromatography (GPC) (a calibration curve is created using polystyrene as a standard).
[0069] According to an embodiment of the present disclosure, the third composition may be composed of a first monomer, a second monomer, and an initiator. According to an embodiment of the present disclosure, the initiator can cause a polymerization reaction to proceed on the acrylate group (methacrylate group or alkenyl group) of the first monomer or / and the acrylate group (methacrylate group or alkenyl group) of the second monomer. For example, the initiator may be a photoinitiator, a thermal initiator, or a combination thereof. According to embodiments of the present disclosure, the content of the initiator can be about 0.01 wt% to 20 wt% (e.g., 0.1 wt%, 0.5 wt%, 1 wt%, 2 wt%, 3 wt%, 4 wt%, 5 wt%, 6 wt%, 7 wt%, 8 wt%, 9 wt%, 10 wt%, 11 wt%, 12 wt%, 13 wt%, 14 wt%, 15 wt%, 16 wt%, 17 wt%, 18 wt%, or 19 wt%) based on the total weight of the first monomer and the monomers.
[0070] According to an embodiment of the present disclosure, the third composition can be reacted at 20° C. to 150° C. for 60 minutes to 24 hours to cause the third composition to undergo a copolymerization reaction to obtain a third polymer (A3).
[0071] According to an embodiment of the present disclosure, the initiator may be a free radical polymerization initiator. According to an embodiment of the present disclosure, the initiator may be a benzoin-based compound, an acetophenone-based compound, a thioxanthone-based compound, a ketal compound, a benzophenone-based compound, an α-aminoacetophenone compound, an acylphosphine oxide compound, a biimidazole-based compound, a triazine-based compound, or a combination thereof. The benzoin-based compound may be, for example, benzoin, benzoin methyl ether, or benzyl dimethyl ketal. Examples of the acetophenone compounds include p-dimethylamino-acetophenone, α,α'-dimethoxydimethoxyazoxy-acetophenone, 2,2'-dimethyl-2-phenyl-acetophenone, p-methoxy-acetophenone, 2-methyl-1-(4-methylthiophenyl)-2-morpholino-1-propanone, and the like. -1-(4-methylthiophenyl)-2-morpholino-1-propanone), 2-benzyl-2-N,N-dimethylamino-1-(4-morpholinophenyl)-1-butanone, and the benzophenone compounds are, for example, benzophenone, 4,4-bis(dimethylamino)benzophenone, 4,4-bis(diethylamino)benzophenone, and the like.4-bis(diethylamino)benzophenone, 2,4,6-trimethylaminobenzophenone, methyl-o-benzoyl benzoate, 3,3-dimethyl-4-methoxybenzophenone, and 3,3,4,4-tetra(t-butylperoxycarbonyl)benzophenone. The thioxanthone compounds are, for example, thioxanthone, 2,4-diethyl-thioxanthone, 2,4 -diethyl-thioxanthanone, and thioxanthone-4-sulfone. Examples of the biimidazole compounds include 2,2'-bis(o-chlorophenyl)-4,4',5,5'-tetraphenyl-biimidazole, 2,2'-bis(o-fluorophenyl)-4,4',5,5'-tetraphenyl-biimidazole, and the like. 2,2'-bis(o-fluorophenyl)-4,4',5,5'-tetraphenyl-biimidazole, 2,2'-bis(o-methylphenyl)-4,4',5,5'-tetraphenyl-biimidazole, 2,2'-bis(o-methoxyphenyl)-4,4',5,5'-tetraphenyl-biimidazole Imidazole [2,2'-bis(o-methoxyphenyl)-4,4',5,5'-tetraphenyl-biimidazole], 2,2'-bis(o-ethylphenyl)-4,4',5,5'-tetraphenyl-biimidazole [2,2'-bis(o-ethylphenyl)-4,4',5,5'-tetraphenyl-biimidazole], 2,2'-bis(p-methoxyphenyl)-4,4',5,5'-tetraphenyl-biimidazole [2,2'-bis(p-methoxyphenyl)-4,4',5,5'-tetraphenyl-biimidazole], 2,2'-bis(2,2',4,4'-tetramethoxyphenyl)-4,4',5,5'-tetraphenyl-biimidazole], 2,2'-bis(2-chlorophenyl)-4,4',5,5'-tetraphenyl-biimidazole[2,2'- bis(2-chlorophenyl)-4,4',5,5'-tetraphenyl-biimidazole], 2,2'-bis(2,4-dichlorophenyl)-4,4',5,5'-tetraphenyl-biimidazole], and the phosphine oxide compound is, for example, 2,4,6-trimethylbenzoyldiphenylphosphine oxide. diphenylphosphine oxide and bis(2,6-dimethoxybenzoyl)-2,4,4-trimethylpentylphosphine oxide, and the triazine compounds are, for example, 3-{4-[2,4-bis(trichloromethyl)-s-triazine-6-yl]pentylthio}propionic acid. acid), 1,1,1,3,3,3-hexafluoroisopropyl-3-{4-[2,4-bis(trichloromethyl)-s-triazine-6-yl]phenylthio}propionate, ethyl-2-{4-[2,4-Bis(trichloromethyl-s-triazine-6-yl]phenylthio}acetate, 2-epoxyethyl-2-{4-[2,4-bis(trichloromethyl)-s-triazine-6-yl]phenylthio}acetate, cyclohexyl-2-{4-[2,4-bis(trichloromethyl)-s-triazine-6-yl]phenylthio}acetate -{4-[2,4-bis(trichloromethyl)-s-triazine-6-yl]phenylthio}acetate, benzyl-2-{4-[2,4-bis(trichloromethyl)-s-triazine-6-yl]phenylthio}acetate, 3-{chloro-4-[2,4-bis(trichloromethyl)-s-triazine-6-yl]phenylthio}propionic acid acid), 3-{4-[2,4-bis(trichloromethyl)-s-triazine-6-yl]phenylthio}propionamide, 2,4-bis(trichloromethyl)-6-p-methoxystyryl-s-triazine, 2,4-bis(trichloromethyl)-6-(1-p-dimethylaminophenyl)-1,3-butanedienyl-s-triazine-butadienyl-s-triazine, or 2-trichloromethyl-4-amino-6-p-methoxystyryl-s-triazine.
[0072] According to an embodiment of the present disclosure, the initiator may be an azo compound, a cyanovaleric-acid-based compound, a peroxide, or a combination thereof. Examples of azo compounds include 2,2'-azobis(2,4-dimethyl valeronitrile), dimethyl-2,2'-azobis(2-methylpropionate), and the like. 2,2'-azobis(2-methylpropionate), 2,2-azoisobutyronitrile (hereinafter referred to as AIBN), 2,2-azobis(2-methylisobutyronitrile), 1,1'-azobis(cyclohexane-1-carbonitrile), 2,2'-azobis[N-(2-propenyl)-2-methylpropionamide] [N-(2-propenyl)-2-methylpropionamide], 1-[(cyano-1-methylethyl)azo]formamide, 2,2'-azobis(N-butyl-2-methylpropionamide), or 2,2'-azobis(N-cyclohexyl-2-methylpropionamide).Examples of peroxides include benzoyl peroxide, 1,1-bis(tert-butylperoxy)cyclohexane, 2,5-bis(tert-butylperoxy)-2,5-dimethylcyclohexane, 2,5-bis(tert-butylperoxy)-2,5-dimethyl-3-cyclohexyne, bis(1-(tert-butylperoxy)-1-methylethyl)benzene, tert-butyl hydroperoxide, tert-butyl peroxide, and tert-butyl peroxybenzoate. peroxybenzoate, cumene hydroperoxide, cyclohexanone peroxide, dicumyl peroxide, or lauroyl peroxide.
[0073] According to an embodiment of the present disclosure, since the electrolyte composition according to the present disclosure contains a polymer having a repeating unit represented by formula (I), a polymer having a three-dimensional network structure can be formed after the electrolyte composition according to the present disclosure is subjected to a heating process to proceed with a ring-opening polymerization reaction. Based on the above, in the electrolyte composition according to the present disclosure, a quasi-solid electrolyte that easily adsorbs lithium salts and solvents in a subsequent heating process can be obtained without the need to add an excessive amount of polymer (component (A)). Therefore, an increase in the interface impedance of the electrolyte and a decrease in the ionic conductivity of the electrolyte due to an excessively large amount of polymer added can be avoided. According to an embodiment of the present disclosure, since the electrolyte composition according to the present disclosure contains a polymer having a repeating unit represented by formula (II), the quasi-solid electrolyte obtained after the electrolyte composition according to the present disclosure is subjected to a ring-opening polymerization reaction has a combustion suppressing property. According to an embodiment of the present disclosure, the content of component (A) can be 1 wt % to 10 wt % (e.g., 2 wt %, 3 wt %, 4 wt %, 5 wt %, 6 wt %, 7 wt %, 8 wt %, or 9 wt %) based on the total weight of components (A), (B), and (C). If the content of component (A) is too high, the ionic conductivity of the resulting quasi-solid electrolyte will be relatively low and the interfacial impedance will be relatively high. If the content of component (A) is too low, the amount of unsolidified residual liquid in the resulting quasi-solid electrolyte will increase, and the combustion suppression will not be enhanced.
[0074] According to an embodiment of the present disclosure, the electrolyte composition according to the present disclosure does not contain any other polymer in addition to component (A). According to an embodiment of the present disclosure, the electrolyte composition according to the present disclosure comprises component (A), component (B) and component (C).
[0075] According to an embodiment of the present disclosure, the electrolyte composition according to the present disclosure does not include a reactive monomer. A reactive monomer refers to a monomer that can form a polymer by a polymerization reaction. According to an embodiment of the present disclosure, the electrolyte composition according to the present disclosure does not include a monomer that can be used to form a polymer having a repeating unit represented by formula (I), and the electrolyte composition according to the present disclosure does not include a monomer that can be used to form a polymer having a repeating unit represented by formula (II).
[0076] According to embodiments of the present disclosure, the weight ratio of the lithium salt (component (B)) to the solvent (component (C)) may be from 1:19 to 7:13, for example, about 2:18, 3:17, 4:16, 5:15, or 6:14. According to an embodiment of the present disclosure, the lithium salt may be any of lithium hexafluorophosphate (LiPF6), lithium perchlorate (LiClO4), lithium bis(fluorosulfonyl)imide lithium (LiN(SO2F)2) (LiFSI), lithium difluoro(oxalato)borate (LiBF2(C2O4)) (LiDFOB), lithium tetrafluoroborate (LiBF4), lithium trifluoromethanesulfonate (LiSO3CF3), lithium bis(trifluoromethane)sulfonimide lithium (LiN(SO2CF3)2) (LiTFSI), lithium bis(trifluoroethane)sulfonimide ... perfluoroethanesulfonimide, LiN(SO2CF2CF3)2), lithium hexafluoroarsenate (LiAsF6), lithium hexafluoroantimonate (LiSbF6), lithium tetrachloroaluminate (LiAlCl4), lithium tetrachlorogallate (LiGaCl4), lithium nitrate (LiNO3), tris(trifluoromethanesulfonyl)methyllithium (LiC(SO2CF3)3), lithium thiocyanate hydrate (LiSCN), LiO3SCF2CF3, LiC6F5SO3, LiO2CCF3, lithium fluorosulfonate,LiSO3F), lithium tetrakis(pentafluorophenyl)borate, LiB(C6H5)4, lithium bis(oxalato)borate, LiB(C2O4)2 (LiBOB), LiFePO4, LiLaTi2O6, Li, 2.9 PO 3.3 N 0.46 , Li3PO4, Li 1.3 Al 0.3 Ti 0.7 (PO4)3, Li 3.6 S 0.6 P 0.4 O4, Li5La3Ta2O 12 , or a combination thereof.
[0077] According to embodiments of the present disclosure, the solvent may be an organic solvent, such as an ester solvent, a ketone solvent, a carbonate solvent, an ether solvent, an alkane solvent, an amide solvent, or a combination thereof. According to an embodiment of the present disclosure, the solvent may be 1,2-diethoxyethane, 1,2-dimethoxyethane, 1,2-dibutoxyethane, tetrahydrofuran, 2-methyl tetrahydrofuran, dimethylacetamide (DMAc), N-methyl-2-pyrrolidone (NMP), methyl acetate, ethyl acetate, methyl butyrate, ethyl butyrate, methyl propionate, ethyl propionate, propyl acetate (PA), butyrolactone (γ-butyrolactone (GBL), ethylene carbonate (EC), propylene carbonate (propylene carbonate ... The carbonate may be selected from the group consisting of ethyl carbonate (PC), diethyl carbonate (DEC), ethylmethyl carbonate (EMC), dimethyl carbonate (DMC), vinylene carbonate, butylene carbonate, 1,3-propanesultone, dipropyl carbonate, or combinations thereof.
[0078] According to an embodiment of the present disclosure, the concentration of the lithium salt (component (B)) in the solvent (component (C)) is about 0.5M to 6M, such as about 0.7M, 0.8M, 0.9M, 1M, 1.2M, 1.3M, 1.4M, 1.5M, 2M, 3M, 4M, or 5M.
[0079] According to an embodiment of the present disclosure, a method for making an electrolyte composition includes mixing component (A), component (B), and component (C). According to an embodiment of the present disclosure, in order to ensure that the electrolyte composition according to the present disclosure is converted into a quasi-solid electrolyte by a ring-opening polymerization reaction, the electrolyte composition according to the present disclosure may further include a component (D), which may be a ring-opening polymerization initiator, and the content of the component (D) may be 0.1 wt % to 20 wt % (e.g., 0.2 wt %, 0.5 wt %, 1 wt %, 2 wt %, 3 wt %, 4 wt %, 5 wt %, 6 wt %, 7 wt %, 8 wt %, 9 wt %, 10 wt %, 11 wt %, 12 wt %, 13 wt %, 14 wt %, 15 wt %, 16 wt %, 17 wt %, 18 wt %, or 19 wt %) relative to the total weight of the components (A), (B), (C), and (D). According to an embodiment of the present disclosure, the electrolyte composition according to the present disclosure comprises component (A), component (B), component (C), and component (D).
[0080] According to an embodiment of the present disclosure, the ring-opening polymerization initiator may be an ionic compound, and the ring-opening polymerization initiator is different from the lithium salt of component (B). According to an embodiment of the present disclosure, the cation of the ionic compound is Na + , Li + , K + , Ag + , or NH4 + and the anion of the ionic compound may be HCOO - , O.H. - , BF4 - , PF6 - , ClO4 - , N(SO2F)2 - , N(SO2CF3)2 - , N(SO2CF2CF3)2 - , BF2(C2O4) - , AsF6 -, or SbF6 - It may be.
[0081] According to an embodiment of the present disclosure, the lithium salt of component (B) is selected from the group consisting of lithium trifluoromethanesulfonate (LiSO3CF3), lithium tetrachloroaluminate (LiAlCl4), lithium tetrachlorogallate (LiGaCl4), lithium nitrate (LiNO3), tris(trifluoromethanesulfonyl)methyllithium (LiC(SO2CF3)3), lithium thiocyanate hydrate (LiSCN), LiO3SCF2CF3, LiC6F5SO3, LiO2CCF3, lithium fluorosulfonate (LiSO3F), lithium tetrakis(pentafluorophenyl)borate (LiB(C6H5)4), lithium bis(oxalato)borate (lithium ... bis(oxalato)borate,LiB(C2O4)2)(LiBOB), LiFePO4, LiLaTi2O6, Li 2.9 PO 3.3 N 0.46 , Li3PO4, Li 1.3 Al 0.3 Ti 0.7 (PO4)3, Li 3.6 S 0.6 P 0.4 O4, or Li5La3Ta2O 12 In the case where the electrolyte composition according to the present disclosure includes the component (A), the electrolyte composition according to the present disclosure may further include a component (D).
[0082] According to an embodiment of the present disclosure, the lithium salt of component (B) is selected from the group consisting of lithium hexafluorophosphate (LiPF6), lithium perchlorate (LiClO4), lithium difluoro(oxalato)borate (LiBF2(C2O4)) (LiDFOB), lithium tetrafluoroborate (LiBF4), bis(fluorosulfonyl)imide lithium (LiN(SO2F)2) (LiFSI), bis(trifluoromethane)sulfonimide lithium (LiN(SO2CF3)2) (LiTFSI), lithium bisperfluoroethanesulfonimide (LiTFSI), lithium bis(fluoroethanesulfonimide) ... When perfluoroethanesulfonimide, LiN(SO2CF2CF3)2), lithium hexafluoroarsenate (LiAsF6), or lithium hexafluoroantimonate (LiSbF6) is contained, the electrolyte composition according to the present disclosure does not need to contain component (D).
[0083] According to an embodiment of the present disclosure, the electrolyte composition according to the present disclosure may further include component (E), which may be a filler, and the content of component (E) may be 0.1 wt% to 30 wt% (e.g., 0.5 wt%, 1 wt%, 2 wt%, 4 wt%, 6 wt%, 8 wt%, 10 wt%, 12 wt%, 14 wt%, 16 wt%, 18 wt%, 20 wt%, 22 wt%, 24 wt%, 26 wt%, 28 wt%, or 29 wt%) based on the total weight of components (A), (B), (C), and (E) (or the total weight of components (A), (B), (C), (D), or (E)). According to an embodiment of the present disclosure, the electrolyte composition according to the present disclosure consists of components (A), (B), (C), (D), and (E).
[0084] According to an embodiment of the present disclosure, the purpose of adding a filler to the electrolyte composition of the present disclosure is to enhance the mechanical strength, increase the ionic conductivity, and improve the safety of the electrolyte. The filler can be titanium oxide, aluminum oxide, zinc oxide, zirconium oxide, silicon oxide, lithium lanthanum zirconate (LLZO), lithium lanthanum titanate (LLTO), lithium aluminum germanium phosphate (LAGP), lithium aluminum titanium phosphate (LATP), or a combination thereof.
[0085] According to an embodiment of the present disclosure, the present disclosure also provides a quasi-solid electrolyte, which is a product of ring-opening polymerization of the electrolyte composition of the present disclosure. A method for preparing the quasi-solid electrolyte of the present disclosure may include carrying out a heating process on the electrolyte composition of the present disclosure (the temperature may be 20° C. to 150° C., and the time may be 60 minutes to 24 hours) to cause ring-opening polymerization of the polymer having the repeat unit of formula (I) (e.g., the first polymer (A1) or the third polymer (A3)) to obtain the quasi-solid electrolyte of the present disclosure.
[0086] According to an embodiment of the present disclosure, a lithium ion battery including the above quasi-solid electrolyte is also provided. See FIG. 1. The lithium ion battery 100 includes an anode 10, a cathode 20, and a separator 30, and the anode 10 is separated from the cathode 20 by the separator 30. According to an embodiment of the present disclosure, the battery 100 may include a quasi-solid electrolyte 40, and the electrolyte 40 is disposed between the anode 10 and the cathode 20. That is, the mutual stack structure of the anode 10, the separator 30, and the cathode 20 is located in the quasi-solid electrolyte 40. According to an embodiment of the present disclosure, the quasi-solid electrolyte is distributed throughout the battery 100. According to an embodiment of the present disclosure, a method for fabricating a lithium ion battery according to the present disclosure may include the following steps. First, the laminate composed of the anode 10, the cathode 20, and the separator 30 is placed in a battery chamber. Then, the electrolyte composition according to the present disclosure is injected into the battery chamber. Finally, the electrolyte composition is subjected to a heating process to transform the electrolyte composition into a quasi-solid electrolyte 40.
[0087] According to an embodiment of the present disclosure, the negative electrode 10 includes a negative electrode active layer, and the negative electrode active layer includes a negative electrode active material. According to an embodiment of the present disclosure, the negative electrode active material can be lithium metal, lithium alloy, transition metal oxide, mesocarbon microbeads (MCMB), carbon nanotubes (CNT), graphene, coke, graphite (e.g., artificial graphite, natural graphite), carbon black, carbon fiber, mesophase carbon microbeads, glassy carbon, lithium-containing compounds, silicon-containing compounds, tin, tin-containing compounds, or combinations thereof. According to an embodiment of the present disclosure, the lithium-containing compounds include LiAl, LiMg, LiZn, Li3Bi, Li3Cd, Li3Sb, Li4Si, Li 4.4 Pb, Li 4.4 Sn, LiC6, Li3FeN2, Li 2.6 Co 0.4 N, or Li 2.6 Cu 0.4According to an embodiment of the present disclosure, the silicon-containing compound may include silicon oxide, carbon-modified silicon oxide, silicon carbon or pure silicon material, or a combination thereof. According to an embodiment of the present disclosure, the tin-containing compound may include tin antimony alloy (SnSb) and tin oxide (SnO). According to an embodiment of the present disclosure, the transition metal oxide may include Li4Ti5O 12 , or TiNb2O7. According to an embodiment of the present disclosure, the lithium alloy may be, for example, an aluminum-lithium-containing alloy, a lithium-magnesium-containing alloy, a lithium-zinc-containing alloy, a lithium-lead-containing alloy, or a lithium-tin-containing alloy.
[0088] According to an embodiment of the present disclosure, the negative electrode active layer may further include a conductive additive, which may be, for example, carbon black, conductive graphite, carbon nanotubes, carbon fibers, or graphene. According to an embodiment of the present disclosure, the negative electrode active layer may further include a binder, which may include polyvinyl alcohol, polytetrafluoroethylene, sodium carboxymethyl cellulose, polyvinylidene fluoride, polystyrene butadiene copolymer, fluorine rubber, polyurethane, polyvinylpyrrolidone, polyethyl acrylate, polyvinyl chloride, polyacrylonitrile, polybutadiene, polyacrylic acid, or a combination thereof.
[0089] According to an embodiment of the present disclosure, the negative electrode 10 may further include a negative electrode current collecting layer, and the negative electrode active layer is disposed on the negative electrode current collecting layer. According to an embodiment of the present disclosure, the negative electrode active layer may be disposed between the separator and the negative electrode current collecting layer. According to an embodiment of the present disclosure, the negative electrode current collecting layer may be a conductive carbon substrate, a metal foil, or a metal material having a porous structure, such as carbon cloth, carbon felt, or carbon paper, copper foil, nickel foil, aluminum foil, nickel mesh, copper mesh, molybdenum mesh, nickel foam, copper foam, or molybdenum foam. According to an embodiment of the present disclosure, the porosity of the metal material having a porous structure may be about 10% to 99.9% (e.g., about 60% or 70%).
[0090] According to an embodiment of the present disclosure, the negative electrode active layer can be prepared and obtained by the negative electrode slurry. According to an embodiment of the present disclosure, the negative electrode slurry can include a negative electrode active material, a conductive additive, a binder, and a solvent, and the negative electrode active material, the conductive additive, and the binder are dispersed in the solvent. The solid content of the negative electrode slurry can be 40wt% to 80wt%. According to an embodiment of the present disclosure, the preparation method of the negative electrode can include the following steps: First, the negative electrode slurry is formed on the surface of the negative electrode current collecting layer by a coating process to form a coating layer. Then, the coating layer is subjected to a drying process (the process temperature can be 50°C to 180°C) to obtain a negative electrode having a negative electrode active layer. According to an embodiment of the present disclosure, the solvent may be N-methylpyrrolidone (NMP), N,N-dimethylformamide (DMF), N,N-dimethylacetamide (DMAc), pyrrolidone, N-dodecylpyrrolidone, γ-butyrolactone, water, or a combination thereof. According to an embodiment of the present disclosure, the coating process may be screen printing, spin coating, bar coating, blade coating, roller coating, solvent casting, or dip coating.
[0091] According to an embodiment of the present disclosure, in the negative electrode active layer, based on the total weight of the negative electrode active material, the conductive additive, and the binder, the weight percentage of the negative electrode active material can be about 80 wt % to 99.8 wt %, the weight percentage of the conductive additive can be about 0.1 wt % to 10 wt %, and the weight percentage of the binder can be about 0.1 wt % to 10 wt %.
[0092] According to an embodiment of the present disclosure, the cathode 20 includes a cathode active layer, and the cathode active layer includes a cathode active material. According to an embodiment of the present disclosure, the cathode active material may be sulfur, an organic sulfide, a sulfur-carbon composite, a metal-containing lithium oxide, a metal-containing lithium sulfide, a metal-containing lithium selenide, a metal-containing lithium telluride, a metal-containing lithium phosphide, a metal-containing lithium silicide, a metal-containing lithium boride, or a combination thereof. Among these, the metal is at least one selected from the group consisting of aluminum, vanadium, titanium, chromium, copper, molybdenum, niobium, iron, nickel, cobalt, and manganese. According to an embodiment of the present disclosure, the positive electrode active material may be any of lithium cobalt oxide, lithium nickel oxide, lithium manganese oxide, lithium cobalt manganese oxide, lithium nickel cobalt oxide, lithium manganese nickel oxide, lithium nickel manganese cobalt oxide, lithium cobalt phosphate, lithium-chromium-manganese oxide, lithium-nickel-vanadium oxide, lithium-manganese-nickel oxide, lithium-cobalt-vanadium oxide, lithium-nickel-aluminum oxide, lithium-nickel-cobalt ... The lithium phosphate may be lithium iron oxide, lithium iron phosphate, lithium manganese iron phosphate, or a combination thereof.
[0093] According to an embodiment of the present disclosure, the positive electrode active layer may further include a conductive additive, which may be, for example, carbon black, conductive graphite, carbon nanotubes, carbon fibers, or graphene. According to an embodiment of the present disclosure, the positive electrode active layer may further include a binder, which may include polyvinyl alcohol, polytetrafluoroethylene, sodium carboxymethyl cellulose, polyvinylidene fluoride, polystyrene butadiene copolymer, fluororubber, polyurethane, polyvinylpyrrolidone, polyethyl acrylate, polyvinyl chloride, polyacrylonitrile, polybutadiene, polyacrylic acid, or a combination thereof.
[0094] According to an embodiment of the present disclosure, the positive electrode may further include a positive electrode current collecting layer, and the positive electrode active layer is disposed on the positive electrode current collecting layer. According to an embodiment of the present disclosure, the positive electrode active layer may be disposed between the separator and the positive electrode current collecting layer. According to an embodiment of the present disclosure, the positive electrode current collecting layer may be a conductive carbon material, a metal foil, or a metal material having a porous structure, such as carbon cloth, carbon felt, or carbon paper, copper foil, nickel foil, aluminum foil, nickel mesh, copper mesh, molybdenum mesh, nickel foam, copper foam, or molybdenum foam. According to an embodiment of the present disclosure, the porosity of the metal material having a porous structure may be about 10% to 99.9% (e.g., about 60% or 70%).
[0095] According to an embodiment of the present disclosure, the positive electrode active layer can be prepared and obtained by a positive electrode slurry. According to an embodiment of the present disclosure, the positive electrode slurry can include a positive electrode active material, a conductive additive, a binder, and a solvent, and the positive electrode active material, the conductive additive, and the binder are dispersed in the solvent. The solid content of the positive electrode slurry can be 40wt% to 80wt%. According to an embodiment of the present disclosure, the preparation method of the positive electrode can include the following steps: First, the positive electrode slurry is formed on the surface of the positive electrode current collecting layer by a coating process to form a coating layer. Then, the coating layer is subjected to a drying process (the process temperature can be 90°C to 180°C) to obtain a positive electrode having a positive electrode active layer. According to an embodiment of the present disclosure, the solvent may be N-methylpyrrolidone (NMP), N,N-dimethylformamide (DMF), N,N-dimethylacetamide (DMAc), pyrrolidone, N-dodecylpyrrolidone, γ-butyrolactone, or a combination thereof. According to an embodiment of the present disclosure, the coating process may be screen printing, spin coating, bar coating, blade coating, roller coating, solvent casting, or dip coating.
[0096] According to an embodiment of the present disclosure, in the positive electrode active layer, based on the total weight of the positive electrode active material, the conductive additive, and the binder, the weight percentage of the positive electrode active material can be about 80 wt % to 99.8 wt %, the weight percentage of the conductive additive can be about 0.1 wt % to 10 wt %, and the weight percentage of the binder can be about 0.1 wt % to 10 wt %.
[0097] According to an embodiment of the present disclosure, the separator 30 may be an insulating material, such as polyethylene (PE), polypropylene (PP), polytetrafluoroethylene film, polyamide film, polyvinyl chloride film, polyvinylidene fluoride film, polyaniline film, polyimide film, polyethylene terephthalate (PS), polystyrene (PS), cellulose, or a combination thereof. For example, the separator may be, for example, a PE / PP / PE multi-layer composite structure. According to an embodiment of the present disclosure, the thickness of the separator is not particularly limited, and a person skilled in the art can adjust it according to actual needs. According to an embodiment of the present disclosure, as an example, the thickness of the separator 30 may be about 1 μm to 1000 μm (for example, about 10 μm, 50 μm, 100 μm, 200 μm, 300 μm, 400 μm, 500 μm, 600 μm, 700 μm, 800 μm, or 900 μm). If the separator is too thick, the energy density of the battery will decrease, while if it is too thin, the mechanical strength of the membrane material will be insufficient, increasing the risk of short circuits between the positive and negative electrodes, increasing the self-discharge phenomenon of the battery, and affecting the cycle stability of the battery.
[0098] In the following, exemplary embodiments will be described in detail with reference to the accompanying drawings so that those skilled in the art can easily understand. The concept of the present invention is not limited to the exemplary embodiments shown herein, but may be embodied in various forms. For clarity, descriptions of known parts will be omitted, and similar reference numerals will refer to similar components throughout. EXAMPLES
[0099] Preparation of polymer
[0100] Preparation example 1
[0101] 100 parts by weight of glycidyl methacrylate (GMA) was dissolved in 100 parts by weight of methyl ethyl ketone (MEK), and 3 parts by weight of azoisobutyronitrile (AIBN) was added as an initiator to obtain a mixture. The mixture was then subjected to a heating process (process temperature was 70°C) to cause free radical polymerization reaction of glycidyl methacrylate. After 24 hours of reaction, the obtained product was cooled to room temperature, and the obtained product was mixed with diethyl ether (volume ratio of the obtained product to diethyl ether was 1:20). After thorough mixing and standing, the precipitated solid was collected and dried to obtain polymer (1).
[0102] The weight average molecular weight of the obtained polymer (1) was measured and found to be about 24,000 (g / mol). The weight average molecular weight was measured using a gel permeation chromatography apparatus (GPC) (model number RI Model 2414). The polymer (1) was then analyzed by nuclear magnetic resonance spectroscopy. The obtained spectral data was as follows: 1 H NMR (CDCl3,500MHz)4.23-4.51(m),3.72-3.92(m),3.12-3.35(s),2.79-2.93(s),2.58-2.74(s),0.78-2.18(m).
[0103] Example 2
[0104] Diethyl 2-(methacryloyloxy)ethyl phosphate, structure is [ka] 100 parts by weight of 1,2-dichloro-2,4-diphenyl ether (DHA) was dissolved in 100 parts by weight of methyl ethyl ketone (MEK), and 3 parts by weight of azoisobutyronitrile (AIBN) was added as an initiator to obtain a mixture. The mixture was then subjected to a heating process (process temperature: 70° C.) to cause a free radical polymerization reaction of diethyl methacryloyloxyethyl phosphate. After 24 hours of reaction, the product was cooled to room temperature and mixed with diethyl ether (volume ratio of the product to diethyl ether: 1:20). After thorough mixing and standing, the precipitated solid was collected and dried to obtain polymer (2).
[0105] The weight average molecular weight of the obtained polymer (2) was measured and found to be about 6000 (g / mol). The polymer (2) was then analyzed by nuclear magnetic resonance spectroscopy. The obtained spectral data was as follows: 1 H NMR (CDCl3,500MHz)4.09-4.27(m),0.78-2.18(m).
[0106] Preparation example 3
[0107] Diphenyl 2-(methacryloyloxy)ethyl phosphate, structure is [ka] 100 parts by weight of 1,2-diphenyl methacryloyloxyethyl phosphate was dissolved in 100 parts by weight of methyl ethyl ketone (MEK), and 3 parts by weight of azoisobutyronitrile (AIBN) was added as an initiator to obtain a mixture. The mixture was then subjected to a heating process (process temperature: 70° C.) to cause a free radical polymerization reaction of diphenyl methacryloyloxyethyl phosphate. After 24 hours of reaction, the product was cooled to room temperature and mixed with diethyl ether (volume ratio of the product to diethyl ether: 1:20). After thorough mixing and standing, the precipitated solid was collected and dried to obtain polymer (3).
[0108] Preparation Example 4
[0109] (6-Oxido-6H-dibenz[c,e][1,2]oxaphosphorin-6-yl)methyl methacrylate, structure is [ka] 100 parts by weight of 6-(6-oxo-6H-dibenz[c,e][1,2]oxaphosphorin-6-yl)methyl methacrylate was dissolved in 100 parts by weight of methyl ethyl ketone (MEK), and 3 parts by weight of azoisobutyronitrile (AIBN) was added as an initiator to obtain a mixture. The mixture was then subjected to a heating process (process temperature: 70° C.) to cause a free radical polymerization reaction to proceed to (6-oxido-6H-dibenz[c,e][1,2]oxaphosphorin-6-yl)methyl methacrylate. After 24 hours of reaction, the product was cooled to room temperature and mixed with diethyl ether (volume ratio of the product to diethyl ether: 1:20). After thorough mixing and standing, the precipitated solid was collected and dried to obtain polymer (4).
[0110] Preparation example 5
[0111] 50 parts by weight of glycidyl methacrylate (GMA) and diethyl 2-(methacryloyloxy)ethyl phosphate (structure: [ka] 50 parts by weight of glycidyl methacrylate was dissolved in 100 parts by weight of methyl ethyl ketone (MEK), and 3 parts by weight of azoisobutyronitrile (AIBN) was added as an initiator to obtain a mixture. The mixture was then subjected to a heating process (process temperature was 70° C.) to cause a free radical polymerization reaction of glycidyl methacrylate and diethyl methacryloyloxyethyl phosphate. After 24 hours of reaction, the product was cooled to room temperature and mixed with diethyl ether (volume ratio of the product to diethyl ether was 1:20). After thorough mixing and standing, the precipitated solid was collected and dried to obtain polymer (5).
[0112] The weight average molecular weight of the resulting polymer (5) was measured and found to be about 22,000 (g / mol). The polymer (5) was then analyzed by nuclear magnetic resonance spectroscopy. The spectral data obtained were as follows: 1 H NMR (CDCl3,500MHz)4.23-4.51(m),4.09-4.27(m),3.72-3.92(m),3.12-3.35(s),2.79-2.93(s),2.58-2.74(s),0.78-2.18(m).
[0113] Preparation of electrolyte composition
[0114] Example 1
[0115] An electrolyte composition (1) was obtained by mixing 93 parts by weight of an electrolyte solution (containing LiPF6, ethylene carbonate (EC), ethylmethyl carbonate (EMC), and diethyl carbonate (DEC). The concentration of LiPF6 was 1 M, and the volume ratio of ethylene carbonate (EC), ethylmethyl carbonate (EMC), and diethyl carbonate (DEC) was 3:5:2), 2 parts by weight of a ring-opening polymerization initiator (LiBF2(C2O4)), 2 parts by weight of polymer (1), and 3 parts by weight of polymer (2).
[0116] Example 2
[0117] An electrolyte composition (2) was obtained by mixing 93 parts by weight of an electrolyte solution (containing LiPF6, ethylene carbonate (EC), ethylmethyl carbonate (EMC), and diethyl carbonate (DEC). The concentration of LiPF6 was 1 M, and the volume ratio of ethylene carbonate (EC), ethylmethyl carbonate (EMC), and diethyl carbonate (DEC) was 3:5:2), 2 parts by weight of a ring-opening polymerization initiator (LiBF2(C2O4)), 2 parts by weight of polymer (1), and 3 parts by weight of polymer (3).
[0118] Example 3
[0119] An electrolyte composition (3) was obtained by mixing 93 parts by weight of an electrolyte solution (containing LiPF6, ethylene carbonate (EC), ethylmethyl carbonate (EMC), and diethyl carbonate (DEC). The concentration of LiPF6 was 1 M, and the volume ratio of ethylene carbonate (EC), ethylmethyl carbonate (EMC), and diethyl carbonate (DEC) was 3:5:2), 2 parts by weight of a ring-opening polymerization initiator (LiBF2(C2O4)), 2 parts by weight of polymer (1), and 3 parts by weight of polymer (4).
[0120] Example 4
[0121] An electrolyte composition (4) was obtained by mixing 95 parts by weight of an electrolyte (containing LiPF6, ethylene carbonate (EC), ethylmethyl carbonate (EMC), and diethyl carbonate (DEC). The concentration of LiPF6 was 1 M, and the volume ratio of ethylene carbonate (EC), ethylmethyl carbonate (EMC), and diethyl carbonate (DEC) was 3:5:2), 2 parts by weight of a ring-opening polymerization initiator (LiBF2(C2O4)), and 3 parts by weight of a polymer (5).
[0122] Comparative Example 1
[0123] An electrolyte composition (5) was obtained by mixing 96 parts by weight of an electrolyte solution (containing LiPF6, ethylene carbonate (EC), ethylmethyl carbonate (EMC), and diethyl carbonate (DEC). The concentration of LiPF6 was 1 M, and the volume ratio of ethylene carbonate (EC), ethylmethyl carbonate (EMC), and diethyl carbonate (DEC) was 3:5:2), 2 parts by weight of a ring-opening polymerization initiator (LiBF2(C2O4)), and 2 parts by weight of the polymer (1).
[0124] Preparation of quasi-solid electrolyte
[0125] The electrolyte compositions (1), (2) and (5) were each subjected to a heating process (process temperature: 55°C, time: 14 hours) to cause a ring-opening polymerization reaction of the polymer (1) in the composition, thereby obtaining the quasi-solid electrolytes (1) to (3), respectively.
[0126] Self-extinguishing time test
[0127] One gram each of the quasi-solid electrolytes (1) to (3) was taken and placed in containers with a diameter of 47 mm. Then, the quasi-solid electrolytes (1) to (3) were ignited and burned, and the time from ignition to the extinguishment of the fire for each quasi-solid electrolyte (self-extinguish time (SET), unit: seconds / gram (sec / g)) was recorded. The results are as shown in Table 1. According to the literature J. of Electrochem. Soc. 2002, 149, A6225, SET > 20 is a flammable material, 6 < SET < 20 is a combustion-inhibiting material, and SET < 6 is a flame-resistant material.
[0128]
Table 1
[0129] As can be seen from Table 1, when the electrolyte composition contains only the first polymer according to the present disclosure (i.e., electrolyte composition (5)), the self-extinguish time of the obtained quasi-solid electrolyte was not different from that of the pure electrolyte solution. When the electrolyte composition simultaneously contains the first polymer and the second polymer according to the present disclosure (i.e., electrolyte compositions (1) and (2)), the obtained quasi-solid electrolyte clearly had an effect of suppressing combustion.
[0130] Fabrication of Lithium-Ion Batteries
[0131] Example 5
[0132] The positive electrode slurry of a standard lithium-ion battery (97.3 wt% of NMC811 (LiNi i Mn j Co kO2; where i: 0.83-0.85; j: 0.4-0.5; k: 0.11-0.12) (product code NMC811-S85E, manufactured by Ningbo Rongbaixin Energy Technology Co., Ltd.), 1 wt% Super-P (conductive carbon powder, purchased from Timcal), 1.4 wt% PVDF-5130, and 0.3 wt% carbon nanotubes (product code TUBALL (registered trademark) BATT, purchased from OCSiAl). NMC811-S85E, Super-P, PVDF-5130, carbon nanotubes are uniformly dispersed in N-methylpyrrolidone) were applied to an aluminum foil (to be the positive electrode current collecting layer) (purchased from Safety Enterprises. Thickness 12 micrometers). After drying, a positive electrode was obtained. Next, a graphite electrode (containing an active material disposed on a current collecting substrate. The current collecting substrate is carbon fiber paper, and the active material is natural graphite) was prepared as the negative electrode. Next, a separator (model number: Celgard 2320, Asahi Kasei) was prepared. Next, the negative electrode / separator / positive electrode were arranged in this order to obtain a laminate, and the laminate was wrapped and sealed with an aluminum plastic film, and then placed in a drying oven to dry at 80°C for 2 hours. Then, the pouch cell that had completed the drying process was taken out, and the electrolyte composition (1) was injected into a glove box filled with argon. After sealing, the pouch cell was placed in a constant temperature oven at 55°C for 14 hours to obtain a lithium ion battery (1).
[0133] Example 6
[0134] Standard lithium-ion battery cathode slurry (97.3 wt% NMC811(LiNi i Mn j Co kO2; where i: 0.83-0.85; j: 0.4-0.5; k: 0.11-0.12) (product code NMC811-S85E, manufactured by Ningbo Rongbaixin Energy Technology Co., Ltd.), 1 wt% Super-P (conductive carbon powder, purchased from Timcal), 1.4 wt% PVDF-5130, and 0.3 wt% carbon nanotubes (product code TUBALL (registered trademark) BATT, purchased from OCSiAl). NMC811-S85E, Super-P, PVDF-5130, and carbon nanotubes are all dispersed in N-methylpyrrolidone) were applied to an aluminum foil (to be the positive electrode current collecting layer) (purchased from Safety Enterprises. Thickness 12 micrometers). After drying, a positive electrode was obtained. Next, a graphite electrode (containing an active material disposed on a current collecting substrate. The current collecting substrate is carbon fiber paper, and the active material is natural graphite) was prepared as the negative electrode. Next, a separator (model number: Celgard 2320, Asahi Kasei) was prepared. Next, the negative electrode / separator / positive electrode were arranged in this order to obtain a laminate, and the laminate was wrapped and sealed with an aluminum plastic film, and then placed in a drying oven to dry at 80°C for 2 hours. Then, the pouch cell that had completed the drying process was taken out, and the electrolyte composition (2) was injected into a glove box filled with argon. After sealing, the pouch cell was placed in a constant temperature oven at 55°C for 14 hours to obtain a lithium ion battery (2).
[0135] Example 7
[0136] Standard lithium-ion battery cathode slurry (97.3 wt% NMC811(LiNi i Mn j Co kO2; where i: 0.83-0.85; j: 0.4-0.5; k: 0.11-0.12) (product code NMC811-S85E, manufactured by Ningbo Rongbaixin Energy Technology Co., Ltd.), 1 wt% Super-P (conductive carbon powder, purchased from Timcal), 1.4 wt% PVDF-5130, and 0.3 wt% carbon nanotubes (product code TUBALL (registered trademark) BATT, purchased from OCSiAl). NMC811-S85E, Super-P, PVDF-5130, carbon nanotubes are uniformly dispersed in N-methylpyrrolidone) were applied to an aluminum foil (to be the positive electrode current collecting layer) (purchased from Safety Enterprises. Thickness 12 micrometers). After drying, a positive electrode was obtained. Next, a graphite electrode (containing an active material disposed on a current collecting substrate. The current collecting substrate is carbon fiber paper, and the active material is natural graphite) was prepared as the negative electrode. Next, a separator (model number: Celgard 2320, Asahi Kasei) was prepared. Next, the negative electrode / separator / positive electrode were arranged in this order to obtain a laminate, and the laminate was wrapped and sealed with an aluminum plastic film, and then placed in a drying oven to dry at 80°C for 2 hours. Then, the pouch cell that had completed the drying process was taken out, and the electrolyte composition (4) was injected into a glove box filled with argon. After sealing, the pouch cell was placed in a constant temperature oven at 55°C for 14 hours to obtain a lithium ion battery (3).
[0137] Comparative Example 2
[0138] Standard lithium-ion battery cathode slurry (97.3 wt% NMC811(LiNi i Mn j Co kO2; where i: 0.83-0.85; j: 0.4-0.5; k: 0.11-0.12) (product code NMC811-S85E, manufactured by Ningbo Rongbaixin Energy Technology Co., Ltd.), 1 wt% Super-P (conductive carbon powder, purchased from Timcal), 1.4 wt% PVDF-5130, and 0.3 wt% carbon nanotubes (product code TUBALL (registered trademark) BATT, purchased from OCSiAl). NMC811-S85E, Super-P, PVDF-5130, carbon nanotubes are uniformly dispersed in N-methylpyrrolidone) was applied to an aluminum foil (to be the positive electrode current collecting layer) (purchased from Safety Enterprises. Thickness 12 micrometers). After drying, a positive electrode was obtained. Next, a graphite electrode (containing an active material disposed on a current collecting substrate. The current collecting substrate is carbon fiber paper, and the active material is natural graphite) was prepared as the negative electrode. Next, a separator (model number: Celgard 2320, Asahi Kasei) was prepared. Next, the negative electrode / separator / positive electrode were arranged in this order to obtain a stack, and the stack was wrapped and sealed with an aluminum plastic film, and then placed in a drying oven to dry at 80°C for 2 hours. Then, the pouch cell that had completed the drying process was taken out, and an electrolyte (containing LiPF6, ethylene carbonate (EC), ethylmethyl carbonate (EMC), and diethyl carbonate (DEC). The concentration of LiPF6 was 1M, and the volume ratio of ethylene carbonate (EC), ethylmethyl carbonate (EMC), and diethyl carbonate (DEC) was 3:5:2) was injected into the pouch cell in an argon-filled glove box. After sealing, the package was placed in a thermostatic oven at 55° C. for 14 hours to obtain a lithium ion battery (4).
[0139] Comparative Example 3
[0140] Standard lithium-ion battery cathode slurry (97.3 wt% NMC811(LiNi i Mn j Co kO2; where i: 0.83-0.85; j: 0.4-0.5; k: 0.11-0.12) (product code NMC811-S85E, manufactured by Ningbo Rongbaixin Energy Technology Co., Ltd.), 1 wt% Super-P (conductive carbon powder, purchased from Timcal), 1.4 wt% PVDF-5130, and 0.3 wt% carbon nanotubes (product code TUBALL (registered trademark) BATT, purchased from OCSiAl). NMC811-S85E, Super-P, PVDF-5130, carbon nanotubes are uniformly dispersed in N-methylpyrrolidone) were applied to an aluminum foil (to be the positive electrode current collecting layer) (purchased from Safety Enterprises. Thickness 12 micrometers). After drying, a positive electrode was obtained. Next, a graphite electrode (containing an active material disposed on a current collecting substrate. The current collecting substrate is carbon fiber paper, and the active material is natural graphite) was prepared as the negative electrode. Next, a separator (model number: Celgard 2320, Asahi Kasei) was prepared. Next, the negative electrode / separator / positive electrode were arranged in this order to obtain a laminate, and the laminate was wrapped and sealed with an aluminum plastic film, and then placed in a drying oven to dry at 80°C for 2 hours. Then, the pouch cell that had completed the drying process was taken out, and the electrolyte composition (5) was injected into a glove box filled with argon. After sealing, the pouch cell was placed in a constant temperature oven at 55°C for 14 hours to obtain a lithium ion battery (5).
[0141] Comparative Example 4
[0142] Standard lithium-ion battery cathode slurry (97.3 wt% NMC811(LiNi i Mn j Co kO2; where i: 0.83-0.85; j: 0.4-0.5; k: 0.11-0.12) (product code NMC811-S85E, manufactured by Ningbo Rongbaixin Energy Technology Co., Ltd.), 1 wt% Super-P (conductive carbon powder, purchased from Timcal), 1.4 wt% PVDF-5130, and 0.3 wt% carbon nanotubes (product code TUBALL (registered trademark) BATT, purchased from OCSiAl). NMC811-S85E, Super-P, PVDF-5130, carbon nanotubes are uniformly dispersed in N-methylpyrrolidone) were applied to an aluminum foil (to be the positive electrode current collecting layer) (purchased from Safety Enterprises. Thickness 12 micrometers). After drying, a positive electrode was obtained. Next, a graphite electrode (containing an active material disposed on a current collecting substrate; the current collecting substrate is carbon fiber paper, and the active material is natural graphite) was prepared as the negative electrode. Next, a separator (model number: Celgard 2320, Asahi Kasei) was prepared. Next, the negative electrode / separator / positive electrode were arranged in this order to obtain a stack, and the stack was wrapped and sealed with an aluminum plastic film, and then placed in a drying oven to dry at 80°C for 2 hours. Then, the pouch cell that had completed the drying process was taken out, and the electrolyte composition (2) was injected in a glove box filled with argon. After sealing (without a heating process), a lithium ion battery (6) was obtained.
[0143] Next, the rate discharge capacity at 0.5 / 2C and the discharge retention rate (2C / 0.5C) of the lithium ion batteries (1), (2), (4), and (5) obtained in Examples 5-6 and Comparative Examples 2-3 were measured. The results are shown in Table 2. The capacity retention rate (%) of the lithium ion batteries (1), (2), (4), and (5) obtained in Examples 5-6 and Comparative Examples 2-3 was also measured. The results are shown in Table 2. Regarding the capacity retention rate, the discharge specific capacity at the 1st cycle and the 450th cycle of the battery was measured at a charge / discharge rate of 1C / 1 (at 45°C), and the capacity retention rate (%) at the 450th cycle was calculated.
[0144] [Table 2]
[0145] As can be seen from Table 2, the discharge capacity at 2C of the lithium ion batteries using the quasi-solid electrolyte according to the present disclosure (e.g., lithium ion batteries (1) and (2)) was still greater than 1.5 Ah, and the discharge retention rate (2C / 0.5C) was higher than 90%. In addition, the capacity retention rate at the 450th cycle of the lithium ion batteries using the quasi-solid electrolyte according to the present disclosure (e.g., lithium ion batteries (1) and (2)) was still higher than 85%, achieving the objective of extending the cycle life of the lithium ion battery.
[0146] Next, the rate discharge capacity at 0.5 / 2C and the discharge maintenance rate (2C / 0.5C) of the lithium ion batteries (2) and (6) obtained in Example 6 and Comparative Example 4 were measured. The results are shown in Table 3. In addition, the battery direct current internal resistance (DCIR) was measured for the lithium ion batteries (2) and (6) obtained in Example 6 and Comparative Example 4. The results are shown in Table 3. The direct current internal resistance (DCIR) was measured by fully charging the battery with a current of 1C, leaving it to stand for 1 hour, and then discharging it with a current of 1C for 3 seconds, and calculating the impedance of the battery from the voltage difference.
[0147] [Table 3]
[0148] In Example 6, the electrolyte composition (2) injected into the pouch battery was subjected to a heating process to promote ring-opening polymerization of the reactive functional group of the polymer (1). On the other hand, in Comparative Example 4, the electrolyte composition (2) injected into the pouch battery was not subjected to a heating process. As can be seen from Table 3, the discharge capacity retention rate of the lithium ion battery (6) obtained in Comparative Example 4 was reduced to about 84.7% and the DC internal resistance was increased to about 61.5 mOhms, compared to Example 6.
[0149] Next, the rate discharge capacity at 0.5 / 2C and the discharge maintenance rate (2C / 0.5C) of the lithium ion batteries (1), (3) and (4) obtained in Example 5, Example 7 and Comparative Example 2 were measured. The results are shown in Table 4. Next, the AC internal resistance (ACIR) of the batteries was measured for the lithium ion batteries (1), (3) and (4) obtained in Example 5, Example 7 and Comparative Example 2 using a battery internal resistance meter. The results are shown in Table 4. In addition, high voltage oxidation current measurements were performed for the lithium ion batteries (1), (3) and (4) obtained in Example 5, Example 7 and Comparative Example 2. The results are shown in Table 4. The high voltage oxidation current was measured for the batteries by linear sweep voltammetry (LSV), which is an electrochemical measurement method. The measurement conditions were a scan rate of 10 mV / s, a voltage range of 3.0 V to 5.5 V, and the current value at 5.5 V was recorded.
[0150] [Table 4]
[0151] As can be seen from Table 4, the discharge capacity at 2C of the lithium ion batteries using the quasi-solid electrolyte according to the present disclosure (e.g., lithium ion batteries (1) and (3)) is still greater than 1.5 Ah, the discharge retention rate (2C / 0.5C) is greater than 90%, and the AC internal resistance is less than 13 mΩ. In addition, the oxidation current of the lithium ion batteries using the quasi-solid electrolyte according to the present disclosure (e.g., lithium ion batteries (1) and (3)) was clearly lower than that of Comparative Example 2 (a lithium ion battery not using the quasi-solid electrolyte according to the present disclosure).
[0152] As described above, the quasi-solid electrolyte having a specific composition according to the present disclosure has excellent combustion suppression properties, good electrical properties, and the effect of suppressing high-voltage oxidation reactions, which can further improve the high-voltage operation, rate performance, and safety of lithium-ion batteries, and can also extend the cycle life of lithium-ion batteries.
[0153] It will be apparent that various modifications and variations can be made in the methods and materials disclosed. It is intended that the specification and examples be considered as exemplary only, with a true scope of the disclosure being indicated by the following claims and their equivalents. [Explanation of symbols]
[0154] 100...Lithium-ion battery 10...Negative electrode 20...Positive electrode 30…Separator 40...Pseudo-solid electrolyte
Claims
1. Component (A) is a combination of a first polymer (A1) and a second polymer (A2), or a third polymer (A3), in which the first polymer (A1) has a repeating unit represented by formula (I), the second polymer (A2) has a repeating unit represented by formula (II), and the third polymer (A3) has a repeating unit represented by formula (I) and a repeating unit represented by formula (II); 【Chemistry 1】 (In the formula, R 1 is hydrogen or a methyl group, R 2 is an oxiranyl group, a methyloxiranyl group, a glycidyl group, or a methylglycidyl group; Z 1 is C 1-10 R is an alkanediyl group. 3 is hydrogen or a methyl group, R 4 and R 5 are each independently C 1-10 an alkoxy group, a substituted or unsubstituted phenoxy group, or R 4 is a substituted or unsubstituted phenyl group, R 5 is a substituted or unsubstituted phenoxy group, and R 4 and R 5 forms a six-membered ring together with the phosphorus atom to which it is bonded, and Z 3 teeth 【Chemistry 2】 or 【Chemistry 3】 and Z4 and Z 6 are each independently C 1-10 It is an alkanediyl group. Component (B) which is a lithium salt; Component (C) which is a solvent; Component (D) which is a ring-opening polymerization initiator; An electrolyte composition comprising: The content of component (A) is 1 wt % to 10 wt % based on the total weight of components (A), (B) and (C), The content of the component (D) is 0.1 wt % to 5 wt % based on the total weight of the components (A), (B), (C), and (D), the component (A) is a combination of a first polymer (A1) and a second polymer (A2), and the weight ratio of the first polymer (A1) to the second polymer (A2) is 1:4 to 4:1; the component (A) is the third polymer (A3), and in the third polymer (A3), the ratio of the number of repeating units represented by formula (I) to the number of repeating units represented by formula (II) is 1:4 to 4:1; Electrolyte composition.
2. 2. The electrolyte composition of claim 1, wherein the weight ratio of said component (B) to said component (C) is from 1:19 to 7:
13.
3. 2. The electrolyte composition of claim 1, wherein the formula (II) is any of the following: 【Chemistry 4】 (In the formula, R 3 is hydrogen or a methyl group, Z 3 is C 1-10 Alkanediyl groups, 【Chemistry 5】 or 【Chemistry 6】 And Z 4 , and Z 6 are each independently C 1-10 R is an alkanediyl group. 6 , R 7 , and R 8 are each independently C 1-10 is an alkyl group.
4. 2. The electrolyte composition of claim 1, wherein in the third polymer (A3), the repeating unit represented by formula (I) and the repeating unit represented by formula (II) are arranged in a block or random manner.
5. The electrolyte composition according to claim 1 , wherein the ring-opening polymerization initiator is an ionic compound.
6. A quasi-solid electrolyte which is a product of ring-opening polymerization of the electrolyte composition according to claim 1 .
7. 1. A lithium ion battery, A positive electrode and A negative electrode; a separator disposed between the positive electrode and the negative electrode; an electrolyte provided between the positive electrode and the negative electrode; Including, A lithium ion battery, wherein the electrolyte is the quasi-solid electrolyte according to claim 6.
Citation Information
Patent Citations
Gel polymer electrolyte and lithium secondary battery containing the same
JP2015537352A
Composition for protecting negative electrode for lithium metal battery, and lithium metal battery fabricated using same
US20050042515A1
Polymer electrolyte for lithium battery and lithium battery employing the polymer electrolyte
US20150155594A1
Gel electrolyte for lithium ion secondary batteries, and lithium ion secondary battery
WO2012090855A1
Solid electrolyte composition, electrode sheet for batteries using same and all-solid-state secondary battery
WO2015046314A1